If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -20 = 14x + -21 Reorder the terms: -20 + 15x = 14x + -21 Reorder the terms: -20 + 15x = -21 + 14x Solving -20 + 15x = -21 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. -20 + 15x + -14x = -21 + 14x + -14x Combine like terms: 15x + -14x = 1x -20 + 1x = -21 + 14x + -14x Combine like terms: 14x + -14x = 0 -20 + 1x = -21 + 0 -20 + 1x = -21 Add '20' to each side of the equation. -20 + 20 + 1x = -21 + 20 Combine like terms: -20 + 20 = 0 0 + 1x = -21 + 20 1x = -21 + 20 Combine like terms: -21 + 20 = -1 1x = -1 Divide each side by '1'. x = -1 Simplifying x = -1
| 7+x(4)=16 | | -5n-8=16m | | 4x-5-6=12x-x-4-3x-7 | | 10n=9n+27 | | 24-8x=-2x+-10 | | x-(3x+7)=29 | | d-1=-9 | | 4x+(-4x)-2y+2y=-10+(-12) | | x+26-8x=8-4x | | 3x-6=60 | | q-e-(-2)=7-q | | 36=39 | | x^3-4x^2-11x+2=0 | | (2x+56)=(8x+8) | | 6x-18=30-2x | | w^2+6w+14=0 | | 2(x+8)=2x+16 | | 4.9x^2-93.3x-125=0 | | 4x^2-13x+12=-2x+12 | | -5-3p=-5(1-7p) | | 37-2x=7x+20 | | 5x+18=13x-82 | | (x+3)m=26 | | 3*(4x)+7*(5x)=2x+5 | | 6g+(-4+2g)=1-g | | 4(5+4x)=-31-x | | 3x-(4x+8)=2(16-x) | | P+5p=-12 | | 5x-21=19 | | 2.625(x/8+0.125)=64 | | 4x^2-19x+31=4x+3 | | 14x-8+2x-5=13x-3+2x |